Fostering Students’ Situational Interest in Physics: Results from a Classroom-Based Intervention Study - Brakhage, Henriette; Gröschner, Alexander; Gläser-Zikuda, Michaela; Hagenauer, Gerda (Research in Science Education, 2023)
Research indicates that students’ interest in science decreases during their school years. To counteract this, a quasi-experimental instructional intervention was designed in which we addressed students’ leisure interests to foster their (situational) interest in physics. Students in the intervention group got the opportunity to choose topics matching their leisure interests (e.g. sports, music) and were encouraged to reflect on and discuss the application of principles of semiconductor physics to those topics throughout the intervention with a duration over 11 lessons. The intervention group consisted of 60 students from German high-track schools; another 55 students comprised the control group. The results of a MANCOVA analysis indicate that the instructional intervention succeeded in triggering students’ catch and hold component of situational interest during all four phases of the lesson series. Furthermore, behavioural disengagement developed more positively for students in the intervention group, while no significant effects were found for their behavioural engagement, their interest in physics-related activities in leisure or their general interest in physics classes in school. The results suggest that addressing students’ leisure interests in physics classes can promote their situational interest and reduce their behavioural disengagement in physics.<br
Keywords: Situational interest; Physics instruction; Leisure interests; Self-determination theory; Motivation; Quasi-experiment; Science education